La violencia laboral hacia trabajadores/as de instituciones de salud de la ciudad de Córdoba, Argentina - Gabriel Acevedo; Alejandra Farias; Julieta Sanchez; Yanina Petiti (Universidade do Porto, 2010)
Workplace violence occurs in different types: mobbing, sexual harassment, physical and psychological aggression and discrimination. Research shows that health workers are victims of 25 per cent of the reported cases of workplace violence. In Argentina, the dimension of the problem is little known; therefore, the objective of the present study is to determine the frequency of violence against health workers. A cross-sectional study was designed and a random sample selected; a survey was administered to 336 workers in health facilities in Cordoba. 21.2 per cent of respondents reported having experienced mobbing; 6.2 per cent experienced sexual harassment, while 8.7 per cent and 28.3 per cent suffered physical violence and psychological aggression, respectively. The following conclusions were reached: different types of violence are often present in the centers studied, little investigation has been carried out and the health workers responded that they feel unprotected.